2010
DOI: 10.1590/s0103-50532010000200012
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of 3-alkoxychromones: photocyclisation of 2-aryl-6-chloro-3-{(thiophen-2-yl)methoxy}chromones

Abstract: 1,4-Biradicais gerados da fotoirradiação de cromonos 2-aril-3-[(tiofen-2-il)metóxi] produziram compostos tetraciclicos angulares contendo grupos tienil. A dehidrogenação e contração do anel dos produtos foram também observadas dependendo da densidade elétrica no anel 2-aril.1,4-Biradicals generated upon photo-irradiation of 2-aryl-3-{(thiophen-2-yl)methoxy} chromones produced angular tetracyclic products bearing the thienyl group. The dehydrogenation and ring contraction products were also observed depending u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…the 2′-and 6′-positions of the methoxyphenyl moiety, and (ii) to observe the effect of the propynyloxy group on photoproduct formation in comparison to other functionalities. 31 Irradiation of 5(a-d) in methanol with pyrex-filtered light from a 125 W Hg UV lamp under an N 2 atmosphere furnished two new compounds 6(a-d) and 7(a-d) in each case, as indicated by the thin layer chromatographic examination of their reaction mixtures (Scheme 2). The removal of solvent under reduced pressure and the chromatographic separation of photolysate with increasing proportions of ethyl acetate in ethyl acetate-petroleum ether yielded the xanthenones 6 (35-45%) and the dealkoxylated chromenones 7 (20-24%) as the photoproducts, approximately in the ratio 2 : 1, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…the 2′-and 6′-positions of the methoxyphenyl moiety, and (ii) to observe the effect of the propynyloxy group on photoproduct formation in comparison to other functionalities. 31 Irradiation of 5(a-d) in methanol with pyrex-filtered light from a 125 W Hg UV lamp under an N 2 atmosphere furnished two new compounds 6(a-d) and 7(a-d) in each case, as indicated by the thin layer chromatographic examination of their reaction mixtures (Scheme 2). The removal of solvent under reduced pressure and the chromatographic separation of photolysate with increasing proportions of ethyl acetate in ethyl acetate-petroleum ether yielded the xanthenones 6 (35-45%) and the dealkoxylated chromenones 7 (20-24%) as the photoproducts, approximately in the ratio 2 : 1, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] In view of these and our continuous effort in developing the photochemistry of such molecules, in the present paper we wish to report the results of our investigations on the photolysis of some 4H-chromen-4-ones bearing the propynyloxy moiety at the 3-position and the 3-methoxyphenyl moiety at the 2-position, with the motive to determine the regioselective photocyclisation and other reactions, as elicited earlier in other similar molecules. [15][16][17][30][31][32]…”
Section: Introductionmentioning
confidence: 99%
“…Some results (Kamboj et al, 2010) have also been reported upon the photolysis of 2-aryl-6-chloro-3-{(thiophen-2-yl)methoxy}chromones 53(a-d) and 54(a-b) in a Pyrex filtered light from a 125 W Hg vapor lamp under nitrogen atmosphere (Scheme 13). The major interest in this study was to investigate the effect of thiophene ring at the 3-alkoxy group upon photoproduct formation and also to investigate the possibility of any photo-transposition.…”
Section: (A-e)mentioning
confidence: 96%
“…1,4‐Biradicals generated upon photo‐irradiation of 2‐aryl‐3‐{(thiophen‐2‐yl)methoxy}chromones 83 produced various angular tetracyclic products i. e. the thienoxanthenones 84 and 85 bearing the thienyl group (Scheme ). The dehydrogenation and ring contraction products 85 and 86 respectively were also observed depending upon the electron density on the 2‐aryl ring …”
Section: Photochemical Synthesis Of Oxaxanthenonesmentioning
confidence: 98%
“…The angular tetracyclic xanthenone 54 and 55 products bearing the thienyl group were generated upon photo‐irradiation of 2‐aryl‐3‐{(thiophen‐2‐yl)methoxy} chromones 53 (Scheme ) in dry methanol …”
Section: Photochemical Synthesis Of Oxaxanthenonesmentioning
confidence: 99%